2017
DOI: 10.1149/2.0281711jss
|View full text |Cite
|
Sign up to set email alerts
|

Device Characteristics of AlGaN/GaN HEMTs with p-GaN Cap Layer

Abstract: In this study, AlGaN/GaN high-electron-mobility transistors with a 5-nm p-GaN cap layer were investigated to compare their performance under various activation conditions. Specifically, p-GaN cap layers were activated using rapid thermal annealing at 700°C for 5, 10, and 15 min in an N2 environment before device fabrication. The gate leakage current reduced considerably when the p-GaN cap layer activation time was longer. The measured on/off current ratio was improved to 9 × 107 for a Schottky-gate device with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Introducing a not fully depleted p-doped GaN cap improved the current collapse by screening the HEMT channel from surface potential fluctuations. 40,41 Since defects are the same for both devices in bulk, measuring gate lag directly assesses the variance in the p-GaN extension.…”
Section: Resultsmentioning
confidence: 99%
“…Introducing a not fully depleted p-doped GaN cap improved the current collapse by screening the HEMT channel from surface potential fluctuations. 40,41 Since defects are the same for both devices in bulk, measuring gate lag directly assesses the variance in the p-GaN extension.…”
Section: Resultsmentioning
confidence: 99%
“…A thin i-GaN cap layer is usually used to prevent oxidation and damage to the AlGaN barrier layer and maintain polarization for 2DEG purposes. 25 However, authors in Arulkumaran et al 26…”
Section: Device Descriptionmentioning
confidence: 99%
“…A thin i‐GaN cap layer is usually used to prevent oxidation and damage to the AlGaN barrier layer and maintain polarization for 2DEG purposes 25 . However, authors in Arulkumaran et al 26 demonstrated (with measurement results obtained from their fabricated HEMTs) that their HEMTs with n‐GaN cap layer exhibited good μ (mobility of electrons in 2DEG), g m (transconductance) and I Dmax (maximum drain current) values.…”
Section: Device Descriptionmentioning
confidence: 99%
“…The ohmic contact performance on GaN capped AlGaN/AlN/GaN HEMTs was improved by Wang et al [16] by optimizing the Ti/Al/Mo/Au electrodes. Finally, activated p-GaN cap layers have been demonstrated to increase the breakdown characteristics and reduce the leakage current of AlGaN/GaN HEMTs [17].…”
Section: Introductionmentioning
confidence: 99%